Isolation of the bioactive peptides CCHamide-1 and CCHamide-2 from Drosophila and their putative role in appetite regulation as ligands for G protein-coupled receptors - Ida, Takanori; Takahashi, Tomoko; Tominaga, Hatsumi; Sato, Takahiro; Sano, Hiroko; Kume, Kazuhiko; Ozaki, Mamiko; Hiraguchi, Tetsutaro; Shiotani, Hajime; Terajima, Saki; Nakamura, Yuki; Mori, Kenji; et al. (Frontiers in Endocrinology, 2012)
There are many orphan G-protein-coupled receptors (GPCRs) for which ligands have not yet been identified. One such GPCR is the bombesin receptor subtype 3 (BRS-3). BRS-3 plays a role in the onset of diabetes and obesity. GPCRs in invertebrates are similar to those in vertebrates. Two Drosophila GPCRs (CG30106 and CG14593) belong to the BRS-3 phylogenetic subgroup. Here, we succeeded to biochemically purify the endogenous ligands of Drosophila CG30106 and CG14593 from whole Drosophila homogenates using functional assays with the reverse pharmacological technique, and identified their primary amino acid sequences. The purified ligands had been termed CCHamide-1 and CCHamide-2, although structurally identical to the peptides recently predicted from the genomic sequence searching. In addition, our biochemical characterization demonstrated two N-terminal extended forms of CCHamide-2. When administered to blowflies, CCHamide-2 increased their feeding motivation. Our results demonstrated these peptides actually present as the major components to activate these receptors in living Drosophila. Studies on the effects of CCHamides will facilitate the search for BRS-3 ligands.